Винайдення престижних предків у контексті світогляду міського патриціату Львова XVII ст.: «перші німці» та «двозначні вірмени» в «Потрійному Львові» Ю.Б.Зиморовича - Осіпян, О.Л. (Український історичний журнал, 2013)
Розглядається вигадування престижних предків та колективної генеалогії львівського патриціату у праці Ю.Б.Зиморовича «Потрійний Львів». Досліджено, як за допо- могою цитат із «Ґерманії» Тацита автор наділяє сучасний йому патриціат чеснота- ми, потрібними як для керування містом, так і для нобілітації. Простежено вплив шляхетської моделі (сарматизму) на уявлення міської верхівки про престижне минуле. На прикладі використання Ю.Б.Зиморовичем лише однієї цитати з «Анналів» Тацита продемонстровано ранньомодерні уявлення про вроджені успадковані риси етносів (у даному випадку – вірменів). Досліджується взаємозв’язок соціального та етнічного у створенні образу міської спільноти, зокрема у презентації соціального конфлікту як етнічного (між католицьким патриціатом та вірменським купецтвом). Розглядається, як у своєму творі Ю.Б.Зиморович намагався леґітимізувати прискорення або призупинення соціальної мобільності різних груп населення міста. Простежено вплив розриву 1648–1660 рр. на актуалізацію у суспільному дискурсі понять «вірність/постійність», «двозначність/невизначеність» та «войовничість». This article investigates invention of the prestigious ancestors and construction of collective genealogy of L’viv’s/Lemberg’s urban patriciate in J.B.Zimorowicz’s “Leopolis triplex”. The article examines how J.B.Zimorowicz portrays his contemporary patriciate as having the virtues necessary to govern the city as well as for ennoblement by way of using quotations from the Tacitus’ “Germania”. It also contributes into better understanding of how the nobility’s model – sarmatism – influenced the urban patriciate’s views on the prestigious past. The case study of a single quotation from Tacitus’ “Annales” demonstrates early modern perceptions about the virtues as innate for a given ethnos and inherited by its members through many generations. The article exploits interconnectedness of the social and ethnic in the making of urban community image, in particular in the presentation of a social conflict as an ethnic one (between the Catholic patriciate and Armenian merchants). It analyses how J.B.Zimorowicz tried to legitimate accelerations or delays in the social mobility of different groups of the city’s population in his opus. The break produced by the political and military crisis of 1648–1660 influenced actualization of the concepts of “constancy”, “ambiguity”, and “militancy” in the public discourse. This actualization, in turn, influenced the narrative concept of “Leopolis triplex”, which reflects its author’s attempt to overcome the break and to restore continuity. Thus, the article contributes to the study of the seventeenth-century urban elites’ worldview, including in their understanding of how the past was reshaped for the present purposes.